Early Mobilization in Patients Post Operation for Femur Fracture - Putri, Maulidya Amalia; Oqui, Maximiano; Abiddin, Andi Hayyun (Health Gate, 2024)
A fracture is a break in the continuity of a bone. The injury recovery process may not go perfectly if the patient cannot move after surgery. Of course, this condition will affect the length of time the patient is considered in the emergency clinic. The recovery that medical staff should be able to carry out in patients with post-operative femur fractures is to complete the initial assembly. Early mobilization is an effort to pursue freedom as quickly as possible by directing the victim to follow physiological capabilities. The motivation behind this study was to determine the impact of early preparation practices on postoperative femoral fracture patients. This research was conducted in the Surgery Room at Ngudi Waluyo Wlingi Regional Hospital. The technique used is a quantitative illustrative examination strategy with an overview type. The population was 5 respondents with post-operative femur fractures treated in the work room, who were examined using an all out examination procedure. Information is obtained through perception. Considering the side effects of the review, it was shown that most of the 60% of respondents with post-operative femur fractures were dependent on others. It stands to reason that there is an impact of movement practices in post-operative femur fracture patients that would encourage a longer stay in the emergency clinic. Patients who are recovering from surgery need to start mobilizing as soon as possible to ensure smooth blood flow, speed wound healing, and minimize hospitalization..